Antidiabetic Molecular Mechanisms of Active Compounds from Several Orchids - Evy Yulianti; Ixora Sartika Mercuriani; Lili Sugiyarto; Tzou-Chi Huang (Jurnal Penelitian Pendidikan IPA, 2023)
Hyperglycemia condition that leads to diabetes causes various complications. Various active compounds from plants have been studied for their antidiabetic abilities. One of them is the orchid plant. Besides being used as decoration, orchids contain several active compounds that have been proven to be used in medicine, including diabetes. This article discusses the antidiabetic mechanism of several active compounds obtained from orchids. Publication regarding orchid plant for diabetes were found in databases such as PubMed, Google Scholar, Wiley, Science Direct, Medline, Scopus, and Springer. Keywords used in this study were â€œorchidâ€, â€œdiabetesâ€, â€œhyperglycemiaâ€, â€œcompoundâ€ and â€œherbalâ€. Out of the 447 collected articles (published in the period between 2011 and 2022), 416 were excluded due to non-relevant studies. There were 31 eligible studies included in this article. In conclusion, the antidiabetic mechanisms of the orchid extracts were as antioxidant, anti-inflammatory and anti-glycation agents, increasing insulin action, influencing lipid metabolism, and inhibiting Î±â€‘amylase and Î±â€‘glucosidase activity. Â